1986
DOI: 10.2105/ajph.76.6.667
|View full text |Cite
|
Sign up to set email alerts
|

Maternal marijuana use and neonatal outcome: uncertainty posed by self-reports.

Abstract: To assess the validity of self-reported marijuana use during pregnancy, this study randomly allocated pregnant women into a group who were told their urine would be tested for marijuana, alcohol, and other drugs and another group not so tested. Women told they would be tested reported more marijuana use during pregnancy than did untested women. Moreover, urine assays iden-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…First, the data were derived from self-reports for which there was no objective validation. It can be argued that self-report measurement of substance use during pregnancy is subject to problems of poor instrument design, recall bias, and underreporting (19)(20)(21)(22). The issues involved in women's reluctance to reveal their substance use include the illicit nature of some substances, fear of having their children taken into care, fear of legal consequences, shame, guilt, and recall problems (23).…”
Section: Discussionmentioning
confidence: 99%
“…First, the data were derived from self-reports for which there was no objective validation. It can be argued that self-report measurement of substance use during pregnancy is subject to problems of poor instrument design, recall bias, and underreporting (19)(20)(21)(22). The issues involved in women's reluctance to reveal their substance use include the illicit nature of some substances, fear of having their children taken into care, fear of legal consequences, shame, guilt, and recall problems (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, we identified 5 studies which determined the sensitivity of interview data on cannabis use among pregnant and postpartum women (Table 1). 2024 These studies reported sensitivities ranging from 0.58 to 0.82. Because falsely reporting cannabis use is very unlikely, we assumed specificity to be 1.00 in all analyses.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown improvements in self-reporting if participants are aware of potential laboratory confirmation. 117,118 However, these tests have lower sensitivity in women, especially in pregnant women, and no biomarkers are currently available that are sensitive enough to detect the relatively low levels of alcohol that would still place the fetus at risk. As with case definitions, consistent assessments and groupings of alcohol intake will be essential if data are to be compared between studies.…”
mentioning
confidence: 99%